Detection and identification of begomoviruses from landraces of okra (Abelmoschus esculentus) in Cameroon - Leke, W.N.; Ramsell, J.N.; Titanji, V.P.K.; Legg, James P.; Brown, J.; Ngeve, J.; Njualem, D.; Fondong, V.N.; Kvarnheden, A. (2006)
Virus diseases present major constraints to production of okra (Abelmoschus esculentus) in Cameroon. However, the identity of these viruses had not been determined prior to this study. Detection of begomoviruses in okra using polymerase chain reaction (PCR) has been problematic because of interfering polysaccharides and phenolics. We report the use of FTA® Classic Cards as an effective means of collecting, extracting, storing, and retrieving begomovirus DNA from okra leaf samples. Leaves presenting symptoms of virus attack were collected from okra plants in the south-western rain forest region of Cameroon and pressed onto FTA® Classic Cards. Using PCR and universal begomovirus primers, all 10 symptomatic samples were positive. In contrast, two of 10 samples were positive using extracted total DNA. The virus species were provisionally identified by sequencing 536 nt of the viral coat protein gene (V1). Okra yellow crinkle virus (OkYCV) was detected in all okra samples, with a nucleotide identity of 96-99% to two OkYCV isolates from Mali. One sample contained a mixed infection with OkYCV and Cotton leaf curl Gezira virus (CLCuGV). A phylogenetic analysis showed close grouping of OkYCV isolates from Cameroon and Mali and of CLCuGV isolates from Cameroon, Egypt and the Sudan.